Pengembangan Sistem Informasi Cerdas Career Guidance Berbasis Minat Di Perguruan Tinggi - Haerani, Elin; Syafria, Fadhilah; Muhammad Yusuf Fadhillah (Computer Science and Information Technology, 2024)
The development of an intelligent information system career guidance based on interests is designed to address the difficulties faced by high school graduates in determining their major in higher education. Difficulties often arise due to confusion caused by a lack of guidance and information. To help address this issue, an intelligent interest- based major recommendation information system was developed using the breadth-first search (BFS) method, which consists of 8 interest categories based on the Rothwell-Miller Interest Blank theory (RMIB). This intelligent information system can provide direction and guidance (career guidance) to students in determining the right major according to their interests. Career guidance application services are highly needed by students who are currently in their unstable teenage years, struggling to determine their paths. This system generates output in the form of major recommendations along with related information. The system is built with PHP and MySQL and tested using the user acceptance test (UAT).